(untitled) (European Journal of Pure and Applied Mathematics, 2019)
This study introduces the concept of companion B-algebra and establishes some of its properties. Also, this paper introduces the notions of -subalgebra and -ideal of a companion B-algebra and investigates their relationship. Furthermore, this study establishes some homomorphic properties of -subalgebra and -ideal.